First experiments of anesthesia control with optimized PID tuning. Issue 2 (2020) - Schiavo, Michele; Padula, Fabrizio; Latronico, Nicola; Merigo, Luca; Paltenghi, Massimiliano; Visioli, Antonio
Abstract: In this paper we present and discuss the first experimental results obtained with a recently devised PID control scheme for the propofol and remifentanil coadministration in general anesthesia. In particular, the depth of hypnosis is controlled by considering only the bispectral index scale as the process variable and the extra degree of freedom in the controller is handled by selecting an appropriate ratio between the infusion rates of the two drugs. The parameters of the PID controllers are selected by using a tuning rule obtained through an optimization procedure that exploits the PK/PD model of a set of patients. A gain scheduling approach is used to switch between two sets of tuning parameters, one for the induction phase and the other for the maintenance phase. The experimental results confirm the effectiveness of the overall design approach.